Sparsity-based narrowband interference mitigation in ultra wide-band communication for 5G and beyond. (November 2017) - Sharma, Sanjeev; Bhatia, Vimal; Gupta, Anubha
Highlights: In this paper, a sparsity based narrowband interference (NBI) mitigation method for ultra-wide-band (UWB) system is proposed. Proposed receiver design method exploits distinct characteristics of UWB signal and NBI. The proposed NBI mitigation method does not use any limiter. Hence, it is free from any threshold effect unlike existing methods. The proposed receiver design is versatile and is robust against NBI for future large bandwidth unlicensed and licensed coexisting 5G and beyond communications. Graphical abstract: Abstract: In real operating environments, the performance of low power large bandwidth ultra wide-band (UWB) communication systems suffers due to narrowband interference (NBI) from high power narrowband interferers. Since noise is not spectrally white in the presence of NBI in UWB systems, conventional matched filter based receivers are not optimum in such scenarios. Although NBI mitigation methods have been proposed using NBI subspace and/or limiters for UWB systems, subspace-based approaches are usually not feasible due to no apriori knowledge of the NBI subspace in a real scenario, and the limiter-based approach is also non-optimum. In this paper, we propose a sparsity-based NBI mitigation method that exploits distinct characteristics of UWB signals and NBI, and does not require a limiter. Improved performance of the proposed receiver has been validated via time hopping binary phase shift keying (TH-BPSK) UWB signal transmission in both additive white Gaussian noise and multipath fading channels.